2020
DOI: 10.33094/8.2017.2020.81.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Inflation and Economic Growth in Zimbabwe is there Any Inflation Threshold Level?

Abstract: This study examines the existence of threshold level as well as the relation between inflation and economic growth in Zimbabwe using annual data for the period 1981 to 2018. While the Dynamic Ordinary Least Squares (DOLS) shows that inflation has a negative impact on economic growth and the share of gross capital formation in gross domestic product has positive impact on economic growth, Engle-Granger test shows that there is long-run relationship between the variables. The conditional least squares shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…JES (Jul-Dec, 2023) The exchange rate had a negative correlation with inflation whereas the GDP and broad money had a positive. Tafti 2021) reported that inflation have a significantly negative impact on the economic growth in Pakistan (see also, Haider et al, 2024;Runganga, 2020;Khan & Khan, 2018;Kartikasari, 2017). On the same line, Tafti (2012) examined the determinants of inflation in the Islamic Republic of Iran.…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…JES (Jul-Dec, 2023) The exchange rate had a negative correlation with inflation whereas the GDP and broad money had a positive. Tafti 2021) reported that inflation have a significantly negative impact on the economic growth in Pakistan (see also, Haider et al, 2024;Runganga, 2020;Khan & Khan, 2018;Kartikasari, 2017). On the same line, Tafti (2012) examined the determinants of inflation in the Islamic Republic of Iran.…”
Section: Literature Reviewmentioning
confidence: 98%
“…In the words of Shapiro (1972), inflation is a steady rise in the general price level that results from the increase in the costs of goods and services in an economy over a period of time. However, high inflation is not in benefit of the economy as it has a negative impact on the economic activities of the country (see, Junejo et al, 2021;Runganga, 2020). When the prices of goods and services are continuously rising, then each unit of money in hands of consumers buys less and can leads economy to in unstable position, as people discourages to save larger and investment more.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also discusses the policy implications for supporting agricultural development and leveraging it for broader economic transformation. Runganga and Mhaka (2021). This study examined the influence of agriculture on economic growth in Zimbabwe, using the Autoregressive Distributed Lag (ARDL) estimation technique and data spanning from 1970 to 2018.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
“…While the research did find a correlation between inflation and economic expansion, it concluded that inflation was not a significant contributor to GDP expansion. From 1981 to 2018, Zimbabwe's inflation and GDP growth were studied by Runganga (2020). According to the findings, inflation slows down an economy, but the link is nonlinear, and stable prices boost productivity.…”
Section: The Interplay Between Fluctuating Oil Prices Rising Price Le...mentioning
confidence: 99%